2019
DOI: 10.1177/0284185119873119
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of ankle ultrasound for diagnosing anterior talofibular and calcaneofibular ligament injuries: a meta-analysis

Abstract: Background Ankle ultrasound imaging could be an option with higher priority due to its lack of radiation, and cost- and time-effectiveness. However, previous studies regarding anterior tibiofibular ligament and calcaneofibular ligament injuries have shown varied results. Purpose To evaluate the diagnostic performance of ankle ultrasound for anterior tibiofibular ligament and calcaneofibular ligament injuries. Material and Methods PubMed and EMBASE databases were searched for diagnostic accuracy studies that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Systematic reviews have found USI to be reliable and accurate in the diagnosis of ATFL and calcaneofibular ligament injuries. 48,266,385,386 Specific studies have supported USI with stress testing 150,314 to be useful to further assess the ATFL to identify the type of injury, 44 grade severity of injury, 63 and assess its thickness. 284 Another systematic review found USI to be accurate in identifying foot fractures, 53 and specifically fifth metatarsal, lateral malleolus, and medial malleolus fractures, in those with a foot and/or ankle sprain.…”
Section: Evidence Update and Summarymentioning
confidence: 99%
“…Systematic reviews have found USI to be reliable and accurate in the diagnosis of ATFL and calcaneofibular ligament injuries. 48,266,385,386 Specific studies have supported USI with stress testing 150,314 to be useful to further assess the ATFL to identify the type of injury, 44 grade severity of injury, 63 and assess its thickness. 284 Another systematic review found USI to be accurate in identifying foot fractures, 53 and specifically fifth metatarsal, lateral malleolus, and medial malleolus fractures, in those with a foot and/or ankle sprain.…”
Section: Evidence Update and Summarymentioning
confidence: 99%
“…The sensitivity and specificity of chronic ATFL cases were 98.7% and 94.0%, both better than those of acute ATFL cases at 88.6% and 90.3%, respectively. Radwan et al reported that US can accurately distinguish the degree of ankle sprain and ligament relaxation, ligament tear, ligament thickness, absorbed ligament, and nonunion avulsion fracture, indicating that US is a reliable method for diagnosing CAI and classifying the degree of instability (35). In another systematic review involving 10 articles, both the sensitivity and specificity of US were in the range of 90%–100% (36).…”
Section: Discussionmentioning
confidence: 99%
“…in 2019, the average sensitivity and specificity of ankle ultrasound were 95% and 99%, respectively. [ 23 ] It means that, in case of an injury or lack thereof in the CFL, sonography is capable of providing a reliable diagnosis. Considering the positive and negative predictive values of 50% and 100% for sonography, it can be said that a sonography scan can be as useful as an MRI in detecting or rejecting the rupture cases in the CFL.…”
Section: Methodsmentioning
confidence: 99%